Chemical and biological characterization of polysaccharides from the bark of Avicennia marina - Fang, Xubo; Yin, Xiaoxiong; Yuan, Gaofeng; Chen, Xiaoe (European food research & technology, 2015)
A water-soluble polysaccharide named BGR-S2 from the bark of Avicennia marina was isolated by ultrasonic-assisted extraction with hot water followed by successive chromatographic purification using DEAE-Sepharose Fast-flow and Sephacryl S-300 columns. A symmetrical peak with an average molecular weight of 119 kDa was obtained by high-performance size exclusion chromatography. Chemical analysis revealed that BGR-S2 is mainly composed of galactose, arabinose, rhamnose and glucose with a molar ratio of 6.2:2.3:1.0:0.8. Based on gas chromatographic, infrared spectral, methylation and NMR analysis, BGR-S2 was structurally characterized as 1,4-D-GalpA interspersed with 1,2-L-Rhap and 1,2,4-L-Rhap residues. The branches are composed of 1,5-L-Araf, 1,3,5-L-Araf, 1,3-L-Araf, 1,6-D-Galp, 1,4,6-D-Galp and 1,4-D-Glcp, and attached to the backbone at the O-4 position of Rhap residues. BGR-S2 showed significant anti-complementary activity by using pectic polysaccharide HAM-3-IIb-II from the stem of A. marina and heparin sodium as positive control. This study provides a foundation for the exploration and utilization of the bark of A. marina in possible therapeutic development.